2006
DOI: 10.1364/oe.14.010073
|View full text |Cite
|
Sign up to set email alerts
|

Developments in realistic design for aperiodic Mo/Si multilayer mirrors

Abstract: Aperiodic multilayers have been designed for various applications, using numeric algorithms and analytical solutions, for many years with varying levels of success. This work developed a more realistic model for simulating aperiodic Mo/Si multilayers to be used in these algorithms by including the formation of MoSi 2 . Using a genetic computer code we were able to optimize a 45° multilayer for a large bandpass reflection multilayer that gave good agreement with the model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(31 citation statements)
references
References 9 publications
(9 reference statements)
0
30
0
1
Order By: Relevance
“…A standard periodic multilayer would only have a bandpass of a few eV. To obtain larger bandpass we used an aperiodic multilayer design2526 based on the algorithm published in ref. 27.…”
Section: Methodsmentioning
confidence: 99%
“…A standard periodic multilayer would only have a bandpass of a few eV. To obtain larger bandpass we used an aperiodic multilayer design2526 based on the algorithm published in ref. 27.…”
Section: Methodsmentioning
confidence: 99%
“…This scheme has been extensively applied in the soft x-ray and EUV region to increase both the angular and wavelength bands. [32][33][34][35][36][37][38] Note that the increase of the reflection bandwidth is unavoidably connected to a decrease of the maximum reflectivity, due to the fact that the layer thicknesses do no longer perfectly match the interference conditions. Furthermore, the absorption in the layers can be enhanced for different wavelengths/angles.…”
Section: B Broadband Multilayer Mirrormentioning
confidence: 99%
“…This first attempt, to realize an aperiodic mirror with Ni/SiC multilayer, shows that the simple Ni 5 Si 2 /SiC model is not sufficient. Aquila et al demonstrated the need to include interdiffusion in the development and optimization of aperiodic Mo/Si multilayer structures in the EUV [5]. The need for high precision on each layer thickness in such a coating would require probably an even more complex model to take into account the variations of interdiffusion effects between Ni and SiC as a function of layer thickness.…”
Section: Aperiodic Ni/sic Multilayermentioning
confidence: 99%
“…The emergence of new sources and applications in the EUV and X-ray spectral domains raises more stringent requirements on the quality of multilayer mirrors. There is a real need for multilayers with low roughness and well-controlled interfaces for the design of complex components, such as ultra-short-period multilayers [1][2][3], alternate multilayer gratings [4], EUV broadband mirrors [5] and phase controlled mirrors for attosecond pulses [6], aperiodic broadband mirrors for X-ray optics [7,8] or plasma diagnostics [9,10]. It is well known that interface defects and material chemical stability often limit the theoretical efficiency of such mirrors.…”
Section: Introductionmentioning
confidence: 99%